2020
DOI: 10.1017/ice.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in ambulatory antibiotic prescription rates in South Carolina: Impact of age, gender, and resident location

Abstract: Objective: To examine the temporal trends in ambulatory antibiotic prescription fill rates and to determine the influences of age, gender, and location. Design: Population-based cohort study. Setting: Ambulatory setting in South Carolina. Patients: Patients ≤64 years of age from January 2012 to December 2017. Methods: Aggregated pharmacy claims data for oral antibiotic prescriptions were utilized to estimate community antibiotic presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…4 The overall rate of antibiotic prescribing in ambulatory settings is declining in children as evidenced by recent studies. 2,3,9 Some of this national decline is attributable to reductions in prescribing for acute respiratory conditions of viral origin through educational campaigns of the general public and health care providers, CDC's Get Smart campaign, stricter diagnostic criteria for ARTI, and watchful waiting for nonsevere otitis media in selected children. 4,10 There have been other studies assessing educational interventions combined with quarterly individualized antibiotic prescribing feedback resulting in reduced broad-spectrum antibiotic prescribing for patients with pneumonia and sinusitis, although the effect has not been consistent and antibiotic prescribing improvements reversed immediately after the study conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The overall rate of antibiotic prescribing in ambulatory settings is declining in children as evidenced by recent studies. 2,3,9 Some of this national decline is attributable to reductions in prescribing for acute respiratory conditions of viral origin through educational campaigns of the general public and health care providers, CDC's Get Smart campaign, stricter diagnostic criteria for ARTI, and watchful waiting for nonsevere otitis media in selected children. 4,10 There have been other studies assessing educational interventions combined with quarterly individualized antibiotic prescribing feedback resulting in reduced broad-spectrum antibiotic prescribing for patients with pneumonia and sinusitis, although the effect has not been consistent and antibiotic prescribing improvements reversed immediately after the study conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several recent studies have demonstrated a significant decline in ambulatory antibiotic prescription in children. 2,3 Although few factors have been speculated to explain this pattern, little is known about the impact of influenza vaccination coverage on antibiotic prescription rates in children. 4 The purpose of this population-based retrospective cohort study is to examine the temporal association between influenza vaccination coverage and ambulatory antibiotic prescription rates in children in South Carolina.…”
mentioning
confidence: 99%